Partial trisomy 21 map: Ten cases further supporting the highly restricted Down syndrome critical region (HR‐DSCR) on human chromosome 21. Issue 8 (25th June 2019) - Pelleri, Maria Chiara; Cicchini, Elena; Petersen, Michael B.; Tranebjærg, Lisbeth; Mattina, Teresa; Magini, Pamela; Antonaros, Francesca; Caracausi, Maria; Vitale, Lorenza; Locatelli, Chiara; Seri, Marco; Strippoli, Pierluigi; et al.
Abstract: Background: Down syndrome (DS) is characterized by the presence of an extra full or partial human chromosome 21 (Hsa21). An invaluable model to define genotype‐phenotype correlations in DS is the study of the extremely rare cases of partial (segmental) trisomy 21 (PT21), the duplication of only a delimited region of Hsa21 associated or not to DS. A systematic retrospective reanalysis of 125 PT21 cases described up to 2015 allowed the creation of the most comprehensive PT21 map and the identification of a 34‐kb highly restricted DS critical region (HR‐DSCR) as the minimal region whose duplication is shared by all PT21 subjects diagnosed with DS. We reanalyzed at higher resolution three cases previously published and we accurately searched for any new PT21 reports in order to verify whether HR‐DSCR limits could prospectively be confirmed and possibly refined. Methods: Hsa21 partial duplications of three PT21 subjects were refined by adding array‐based comparative genomic hybridization data. Seven newly described PT21 cases fulfilling stringent cytogenetic and clinical criteria have been incorporated into the PT21 integrated map. Results: The PT21 map now integrates fine structure of Hsa21 sequence intervals of 132 subjects onto a common framework fully consistent with the presence of a duplicated HR‐DSCR, on distal 21q22.13 sub‐band, only in DS subjects and not in non‐DS individuals. No documented exception to the HR‐DSCR model was found. Conclusions: The findings presented here further support the association of the HR‐DSCR with the diagnosis of DS, representing an unbiased validation of the original model. Further studies are needed to identify and characterize genetic determinants presumably located in the HR‐DSCR and functionally associated to the critical manifestations of DS. Abstract : A systematic retrospective reanalysis of 125 PT21 cases described up to 2015 allowed the creation of the most comprehensive PT21 map and the identification of a 34‐kb highly restricted DS critical region (HR‐DSCR) as the minimal region whose duplication is shared by all PT21 subjects diagnosed with DS. We reanalyzed at higher resolution three cases previously published and we accurately searched for any new PT21 reports in order to verify whether HR‐DSCR limits could prospectively be confirmed and possibly refined.The findings presented here further support the association of the HR‐DSCR with the diagnosis of DS, representing an unbiased validation of the original model.